PREPOSISI DALAM KITAB KEJADIAN - KEINTJEM, YEMIMA EUNIKE (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research entitled â€œThe Prepositions in the Book of Genesis in the Bibleâ€ it is written to identify and classify the form and analyze the meaning of the prepositions that is used in the book of Genesis in the Bible. In analyzing the data, the writer used theory based on Aarts and Aarts (1982) to classifying the forms of prepositionsand Curmeâ€™s theory (1986) in analyzing the meaning of prepositions as a part of descriptive method. The data were taken from the book of Genesis in the Bible based on the Holy Bible New International Version, International Bible Society. The form of the prepositions that founded in the Book of Genesis in the Bible, such as simple preposition (one-word preposition) consist of: at, before, from, in, between, by, during, of, on, since, until, and with, whereas complex preposition (multi-word preposition) consist of: according to, as to, because of, in addition to, in front of, and out of. Then, the meaning of the prepositions that founded, consist of: refer to place, time, cause or reason, purpose, source, cause or reason, manner, instrument, participation, characteristic, possessive, amount, measure and conquest. Key words : Prepositions, Form and Meaning, The Book of Genesisin the Bible